2018
DOI: 10.3390/f9060318
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics Analysis of Phytohormone-Related Genes and Alternative Splicing Events Related to Witches’ Broom in Paulownia

Abstract: Paulownia is a native fast-growing tree in China that has been introduced into many countries. However, it is often infected by Paulownia witches' broom (PaWB) disease, which can lead to large declines in yield. PaWB is caused by a phytoplasma that is an obligate biotrophic plant pathogen. Until now, the molecular mechanisms of interactions between the host plants and the phytoplasma have not been clear. In previous studies, it was reported that PaWB-infected Paulownia exhibited healthy morphology after being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Overall, phytoplasma infection unbalanced phytohormone levels in infected plants, which caused various severe symptoms (Dermastia 2019). These findings are in accordance with previous studies reporting several differentially expressed genes (DEGs) encoded proteins associated with JA signal transduction (Dong et al 2018). Meanwhile, the observed variations in phytohormone levels can also be considered as a secondary effect of phytoplasmarelated infection, which might be partially described by suppression of the phloem transport.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, phytoplasma infection unbalanced phytohormone levels in infected plants, which caused various severe symptoms (Dermastia 2019). These findings are in accordance with previous studies reporting several differentially expressed genes (DEGs) encoded proteins associated with JA signal transduction (Dong et al 2018). Meanwhile, the observed variations in phytohormone levels can also be considered as a secondary effect of phytoplasmarelated infection, which might be partially described by suppression of the phloem transport.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, we have investigated the transcriptional changes in P. fortunei under phytoplasma stress, and significantly differentially expressed genes (DEGs) responsive to phytoplasma infection were identified by using the criteria of |log 2 ratio| ≥ 1 and FDR < 0.001 [ 63 ]. Previous studies have proposed that H3K4me3, H3K9ac and H3K36me3 marks are associated with transcriptional activation.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, histone modifications only affected the expression of a small portion of phytoplasma-responsive genes. Among these genes, only a small number of them displayed alterations in histone modification paralleled by the changes in gene expression [ 63 ] in P. fortunei infected with phytoplasma. And some DEGs were found to be co-occupied by more than one histone marks, indicating the possible relevance of the balance of different histone marks to the transcriptional regulation in Paulownia-phytoplasma interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Many differentially expressed genes (DEGs) among these samples were identified. Studies using the gene ortholog (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway databases indicated that these DEGs are involved in various pathways, including phytohormone biosynthesis, photosynthesis and plant-pathogen interaction [51][52][53][54][55][56][57][58].…”
Section: Transcriptional Responsesmentioning
confidence: 99%
“…AS increases transcriptome plasticity and proteome diversity and is an important post-transcriptional regulatory mechanism. Analysis using high-throughput transcriptome sequencing has identified many alternative splicing variants of paulownia mRNAs [56,58,59,65,66]. The AS frequency in healthy paulownia is higher than in PaWB-diseased samples.…”
Section: Splice Variantsmentioning
confidence: 99%